2016
DOI: 10.3109/0284186x.2015.1118656
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement in T-cell lymphoma: A single center experience

Abstract: Background We characterized the incidence of central nervous system (CNS) involvement, risk factors and outcome in a large single institution dataset of peripheral T cell lymphoma (PTCL). Methods Retrospective review of the PTCL database at Memorial Sloan Kettering Cancer Center. We identified 231 patients with any subtype of PTCL between 1994–2011 with a minimum 6 months of follow-up or an event defined as relapse or death. Results Histologies included peripheral T cell lymphoma – no not otherwise specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 20 publications
6
40
2
Order By: Relevance
“…CNS relapse in patients with PTCL is considered a very rare event. In this study, we showed that >1 site of extranodal involvement is significantly associated with risk of CNS relapse, which is in keeping with the results from earlier studies [ 5 7 ]. Interestingly, we also found that risk may vary by histologic type; patients with ALK+ ALCL had higher risk of CNS relapse compared to other types, particularly AITL.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CNS relapse in patients with PTCL is considered a very rare event. In this study, we showed that >1 site of extranodal involvement is significantly associated with risk of CNS relapse, which is in keeping with the results from earlier studies [ 5 7 ]. Interestingly, we also found that risk may vary by histologic type; patients with ALK+ ALCL had higher risk of CNS relapse compared to other types, particularly AITL.…”
Section: Discussionsupporting
confidence: 92%
“…Yi and colleagues reported an even higher incidence of CNS involvement of 8.8% (20/228) in patients with PTCL at a median time to CNS disease of 6.1 months, though they included patients who had CNS involvement at the time of diagnosis [ 7 ]. Most recently, Gurion and colleagues presented data from Memorial Sloan Kettering Cancer Center, showing that 6.5% (15/231) of patients with PTCL had CNS involvement with a median time to CNS disease of 3.4 months, although again the authors included patients who had CNS involvement at the time of diagnosis as well as patients with ATLL; the latter group is well known to have high chance of CNS relapse [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNS involvement by peripheral T‐cell lymphomas generally portends poor prognosis. A recent review from a single institution documented 15 of 231 patients with CNS involvement by a peripheral T‐cell lymphoma over a 17‐year time period, of which 8 cases were pathologically confirmed. CNS disease typically presented early (median, 3.44 months from diagnosis of lymphoma to CNS involvement), and survival thereafter was a median of 2.63 months.…”
Section: Discussionmentioning
confidence: 99%
“…Features associated with a high risk of CNS relapse in diffuse large B-cell lymphoma (DLBCL) include elevated LDH (above institutional normal limit), more than one extranodal site of involvement and specific anatomical sites (testes, breast, paranasal sinus, epidural and bone marrow). Considering its rarity and lack of prospective studies, the British Committee for Standards in Haematology extends the recommendations of using CNS-directed prophylaxis (intrathecal methotrexate (12–15 mg) or systemic methotrexate (3–5 g/m²)) in high-risk DLBCL to PTCL as well 2. Isolated CNS relapse in a case of primary cutaneous ALCL is extremely uncommon.…”
Section: Descriptionmentioning
confidence: 99%